2006
DOI: 10.1179/174329006x89344
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cu3P addition on sintering behaviour of elemental powders in the composition of 465 stainless steel

Abstract: The addition of Cu 3 P for developing the high strength 465 maraging stainless steel from elemental powders was studied. The sintering parameters investigated were sintering temperature, sintering time and wt-%Cu 3 P. In vacuum sintering, effective sintering took place between 1300 and 1350uC. The maximum sintered density of 7 . 44 g cm 23 was achieved at 1350uC for 60 min with 4-6 wt-%Cu 3 P. More than 6 wt-%Cu 3 P content and temperature .1350uC caused slumping of the specimens. The sintered specimens were h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…The hardness of the substrate material was 40.5-41 HRC after sintering. The hardness values for top layer and substrate material after sintering agree well with the previous findings [12,16,[19][20][21]. The overview of the mechanical properties is given in Table 2.The bending strength of the layered materials is measured in the direction perpendicular to the layer alignment.…”
Section: Mechanical Propertiesmentioning
confidence: 53%
See 2 more Smart Citations
“…The hardness of the substrate material was 40.5-41 HRC after sintering. The hardness values for top layer and substrate material after sintering agree well with the previous findings [12,16,[19][20][21]. The overview of the mechanical properties is given in Table 2.The bending strength of the layered materials is measured in the direction perpendicular to the layer alignment.…”
Section: Mechanical Propertiesmentioning
confidence: 53%
“…Recently in our study, we reported that the elemental and pre alloyed powders of 465 stainless steel can approach to 7.44 g/cm 3 and 7.57 g/cm 3 density, respectively, when sintered at 1350 • C for 1 h and exhibit good mechanical properties after sintering process [12]. Fig.…”
Section: Microstructure Of the Compositementioning
confidence: 95%
See 1 more Smart Citation
“…In order to compete with dense 316L parts, high density P/M 316L parts with high mechanical and corrosion properties are required. One of the investigated ways to fabricate high density P/M stainless steel parts is the addition of sintering additives to stainless steel powder [2]. The sintering additives lower the sintering temperature and activate densification mechanisms to eliminate pores.…”
Section: Introductionmentioning
confidence: 99%
“…The sintering additives lower the sintering temperature and activate densification mechanisms to eliminate pores. Sintering additives such as FeB, NiB, FeMoB, Si and Cu 3 P have been reported for the enhanced sintering of stainless steels [2][3][4][5][6][7][8]. These sintering additives activate the sintering process of stainless steel powders by the formation of a liquid phase.…”
Section: Introductionmentioning
confidence: 99%